Reclaiming Social Harmony, Prophetic Paradigm Communication Media as a Sociological Model for Public Relations in Managing Social Communication Issues - Akhmad Muwafik Saleh; Rachmat Kriyantono (DAWUH : Islamic Communication Journal, 2026)
This study explores the role of communication media within the prophetic paradigm as a sociological model for Public Relations (PR) in addressing contemporary social communication problems. Departing from the premise that media is not merely a channel of message delivery but an institution that shapes social realities, this research analyzes how mediatization, commercialization, and sensational framing contribute to the fragmentation of social cohesion. The paper employs a sociological communication framework combined with prophetic values humanization, liberation, and transcendence as formulated by Kuntowijoyo, to offer an ethical corrective to media distortion and distrust. Drawing on Qur’anic principles such as al-Hamāsah, ad-Da’wu Bih, and tabayyun, the study argues that prophetic communication provides a moral and operational model capable of restoring social harmony. The research reveals that media and PR practices rooted in empathy, ethical verification, anti-sensational framing, and public-oriented narratives can reduce polarization, strengthen social trust, and protect communities from digital misinformation. This work proposes the Prophetic Public Relations Model as an alternative framework for reclaiming social harmony by positioning media as a moral mediator, cultural integrator, and guardian of public ethics. Ultimately, this study highlights the transformative potential of prophetic communication in shaping a more ethical, inclusive, and socially cohesive media environment.